Circumcision of HIV-infected men and transmission of human papillomavirus to female partners: analyses of data from a randomised trial in Rakai, Uganda. - Tobian AA; Kong X; Wawer MJ; Kigozi G; Gravitt PE; Serwadda D; Eaton KP; Nalugoda F; Quinn TC; Gray RH; Tobian, Aaron A R; Kong, Xiangrong; et al. (Lancet Infectious Diseases, 2011)
Background: Male circumcision reduces the transmission of high-risk human papillomavirus (HPV) in HIV-uninfected men and their female partners. We assessed whether circumcision of HIV-infected men would reduce the transmission of high-risk HPV to their female partners.Methods: Female partners of HIV-infected men (aged 15-49 years) in Rakai, Uganda, with CD4 counts of greater than 350 cells per mL who were randomly assigned to undergo circumcision immediately (intervention group) and after 24 months (control group) were assessed for infection with high-risk HPV. Randomisation was done in blocks of 20, stratified by community, with computer-generated random numbers. Laboratory technicians and female fieldworkers were masked to the circumcision status of male participants. The main outcome assessed in this study was the effects of circumcision of HIV-infected men on transmission of HPV to their female partners. Analysis was by intention to treat. The trial is registered with ClinicalTrials.gov, number NCT00124878.Findings: 474 men were assigned to the intervention group, 448 to the control group. 211 women were in consensual relationships with 193 men in the intervention group, and 171 women were in consensual unions with 155 men in the control group. High-risk HPV at the 2-year follow-up was prevalent in 88 female partners (55%) of 159 men in the intervention group and 68 (52%) of 131 female partners of men in the control group (prevalence risk ratio 1·07, 95% CI 0·86-1·32, p=0·64). Incidence of high-risk HPV over 2 years was 32·0 per 100 person-years in the female partners of men in the intervention group and 30·6 per 100 person-years in the female partners of men in the control group (incidence rate ratio 1·05, 0·77-1·43, p=0·78). No difference was noted in the clearance of genotype-specific high-risk HPV between the intervention group (196 [46%] of 424) and control group (167 [48%] of 347; rate ratio 0·96, 0·83-1·12; p=0·61).Interpretation: Because circumcision of HIV-infected men did not affect transmission of high-risk HPV to their female partners, promotion of consistent safe sexual practices for HIV-infected men remains important.Funding: Bill & Melinda Gates Foundation and National Institutes of Health.